PENELAAHAN SIFAT PRIORITAS PEMANFAATAN JENIS TANAMAN UNTUK KAYU BAKAR - Rachman Effendi; Suwidji Basuki; Han Roliadi (Jurnal Penelitian Hasil Hutan, 1987)
There is a need to classify fire  wood for flue/  based on energy content.   This research is conducted  to categorized fire wood species using discriminant  analysis.Data of which collected from  each of  research areas are plant  varieties for  fire  wood,  age classification,  annual  volume  increase,   specific gravity,  calor value and volume  of  extractive  elements.Variety of  woods used for fire  wood are Akasia  (Acacia   auriculiformis),   Akasia  (Acacia decurrens),  Kaliandra  (Calliandra  callothyrsus), Gamal  (Gliricidia  maculata),  Kemlandingan   (Leucaena  glauca),  Turi  (Sesbania   grandiflora)   and  Jati  (Tectona  grandis). For  the purpose   of analysis of the type of relationship  between  annual volume  increase (X1), specific  gravity  (X2),  calor value (X3),  volume  of extractive  elements (X4) and the adaptation order of plant  varieties for fire  wood is clasified by the discriminant function.The function is also used for  determining adaptation  order of utilization  of plant  varieties for fire  wood.Based on the discriminant  analysis it can be expressed  as:Yj = 0.2148X1j + 9.7184X2j + 0.7231 X3j - 6.7121 X4j..................................................................(1).                                               The result of average substitutions of annual volume increase, as specific gravity,  ca/or value increase and volume of extractive elements  decreased as described by the equation  (I).  It can be said that (the adaptation  order of plant  varieties for  fire  wood) produced  from   the most  to the least based on its number of heat of combustion  at the plantation  age 2, 3 and 4 years are Akasia   (Acacia decurrens), Akasia  (Acacia auriculiformis), Kaliandra  (Calliandra callethyrsus),   Gamal  (Gliricidia  maculata),  Kemlandingan  (Leucaena   glauca),  Turi  (Sesbania  grandiflora)   and  Jati (Tectona  grandis).